2015
DOI: 10.1007/s11695-015-1830-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Insufficient Weight Loss After Bariatric Surgery: Does Obstructive Sleep Apnea Influence Weight Loss?

Abstract: The presence of OSA does not individually impair weight loss after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…9 Finally, in a sample of 816 bariatric surgery patients, de Raaff and colleagues found that those with OSA at preoperative screening experienced less weight loss at 6 and 12 months following surgery compared to those without OSA, though the strength of the relationship weakened considerably once confounders such as age and baseline BMI were considered. 23 As we found an approximately 2% difference in weight loss between those with and without OSA in a predominantly female sample with mild OSA, our results are in agreement with prior behavioral weight loss interventions and indicate that even mild OSA may impair behavioral weight loss outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…9 Finally, in a sample of 816 bariatric surgery patients, de Raaff and colleagues found that those with OSA at preoperative screening experienced less weight loss at 6 and 12 months following surgery compared to those without OSA, though the strength of the relationship weakened considerably once confounders such as age and baseline BMI were considered. 23 As we found an approximately 2% difference in weight loss between those with and without OSA in a predominantly female sample with mild OSA, our results are in agreement with prior behavioral weight loss interventions and indicate that even mild OSA may impair behavioral weight loss outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the number of comorbidities and previous history of hypertension predicted IWL [36]. Likewise, patients with obstructive sleep apnea achieved significantly lower EWL% at 1 year after surgery than patients with no sleep apnea [86].…”
Section: Preoperative Predictors Of Wr and Iwl Post-bsmentioning
confidence: 89%
“…The presence of comorbidities predicts WR and IWL. For instance, T2D predicted WR and IWL [34,[79][80][81]86]; while hypertension and low HDL cholesterol were both associated with poor weight trajectory [34]. Similarly, the number of comorbidities and previous history of hypertension predicted IWL [36].…”
Section: Preoperative Predictors Of Wr and Iwl Post-bsmentioning
confidence: 99%
“…Recent studies associate bariatric surgery with a considerable long-term insufficient weight loss or complications, with a secondary procedure needed in approximately 20% of patients [3,4]. The initial BMI is a significant predictive factor of insufficient weight loss, with worse weight loss results in patients with a higher initial BMI [5,6]. The treatment of people with severe obesity and BMI > 50 kg/m 2 is challenging for three main reasons: (1) insufficient weight loss is more frequent after bariatric surgery in this setting; (2) surgery is technically more demanding; and (3) surgery is associated with higher postoperative morbi-mortality [7].…”
Section: Introductionmentioning
confidence: 99%